ANALISIS KELAYAKAN FINANSIAL USAHATANI KAKAO DI DESA OGODOPI KECAMATAN KASIMBAR KABUPATEN PARIGI MOUTONG - Siska, Siska; Antara, Made; Christoporus, Christoporus (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2024)
This study aimed to evaluate the financial feasibility of cocoa farming in Ogodopi Village, Kasimbar District, over the period of November to December 2019. The village was selected purposively due to its prominence in cocoa production within the region. A sample of 33 cocoa farmers was chosen from a population of 124 using a simple random sampling technique. Financial feasibility was assessed using Net Present Value (NPV), Net Benefit-Cost Ratio (Net B/C), Internal Rate of Return (IRR), Payback Period (PP), and Sensitivity Analysis. Initial results indicated an NPV of IDR 576,322,972, a Net B/C of 1.33, an IRR of 10%, and a PP of 1.3 years, suggesting financial feasibility. Further sensitivity analysis, considering a potential 10% decrease in production, resulted in an NPV of IDR 858,617,192, a Net B/C of 0.50, an IRR of 39.35%, and a PP of 1.4 years. These findings confirm that cocoa farming in Ogodopi Village remains financially feasible under varying economic conditions.